Methodology for the selection of manufacturing technology chains based on ecologic and economic performance indicators. (February 2023) - Grünert, G.; Grünebaum, T.; Beckers, A.; Stauder, L.; Barth, S.; Bergs, T.
Abstract: When manufacturing products, it becomes increasingly important to consider ecological factors in addition to conventional key performance indicators such as manufacturing costs, time or quality. The greatest leverage for creating the most sustainable form of product manufacture is in the early stages of technology planning, because emissions can be avoided in the long term through the selection of sustainable technologies. However, there are methods that allow ecological factors to be taken into account during technology planning to supplement the usual key performance indicators, but the level of detail and the applicability are not yet sufficient. In order to support decision makers in the planning and evaluation of technology chains, this paper develops a methodology that supports technology chain selection. For this purpose, an economic-ecological key performance indicator was developed which combines manufacturing costs, material flow costs and environmental impacts determined through life cycle assessment to enable a holistic view. Highlights: Consider economy and ecology in the early technology planning for manufacturing. Framework for a LCA of manufacturing processes. Providing Life cycle impact assessment (LCIA) for manufacturing processes. Decision support through a single economic-ecological KPI.